2021
DOI: 10.1515/tjb-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress index can be a new marker related to disease severity in COVID-19

Abstract: Objectives The aim of this study was to evaluate the relationship between systemic oxidative balance, and the severity of the disease in patients with COVID 19. Methods Sixty-four patients were divided into three groups according to the severity of the disease: mild (n=28), moderate (n=11) and severe (n=25). Twenty-four healthy controls included to the study. Proinflammatory cytokines (IL-6 and TNF-α), D-dimer, fibrinogen, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
2
18
0
3
Order By: Relevance
“…These results indicate that IDO activity and the TRYCAT pathway are upregulated in COVID-19 and that it predicts critical disease and non-survival. The most probable cause of IDO enzyme activation in COVID-19 is the increased level of proin ammatory cytokines including IFN-γ, IL-1β and IL-6 [53,54] and activated oxidative stress pathways [55], which both potently stimulate IDO [25,56].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that IDO activity and the TRYCAT pathway are upregulated in COVID-19 and that it predicts critical disease and non-survival. The most probable cause of IDO enzyme activation in COVID-19 is the increased level of proin ammatory cytokines including IFN-γ, IL-1β and IL-6 [53,54] and activated oxidative stress pathways [55], which both potently stimulate IDO [25,56].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of a link between decreased expression of the antioxidant enzyme superoxide dismutase 3 (SOD3) in the lungs of elderly patients with COVID-19 and disease severity [83]. In addition, a low level of glutathione (GSH) and downregulation of glutathione peroxidase (GPX4) gene expression in SARS-CoV-2 infection was found [52,[84][85][86][87]. In detail, in the RBCs from COVID-19 patients, Thomas et al identified a high level of the end product of the PPP that suggests a high degree of oxidative stress also evidenced by an increase in oxidized glutathione (GSSG) [24].…”
Section: Hemolysis and Oxidative Stress In Covid-19mentioning
confidence: 99%
“…Under low oxygen saturation intra-erythrocyte, NO can also react with deoxyhemoglobin generating nitrosyl Hb. NO levels are significantly reduced in COVID-19 patients: this is likely related to vascular dysfunction and inflammation [87,88]. Although SARS-CoV-2, mainly infects the cells of the bronchial epithelium and pulmonary, residual viral particles have also been found in endothelial cells, leading to apoptosis and endothelial decrease in NO [78,93].…”
Section: Intra and Extra-erythrocytic No Levels In Covid-19 Patientsmentioning
confidence: 99%
“…This association has previously been established [ 29 , 30 ] together with elevated pro-inflammatory cytokines in such cases [ 31 ]. These two; elevated proinflammatory cytokines and oxidative stress, have been implicated in pathophysiological events in non-communicable diseases [ 32 34 ] and communicable diseases [ 35 37 ] as well.…”
Section: Discussionmentioning
confidence: 99%